VERIFICATION AND CONTROL OF INTERNATIONAL TREATY REGULATION ON MISSILE-NUCLEAR ARMAMENTS - Myronenko, Vyacheslav (Public Management and Policy, 2025)
In the context of the weakening of international treaties on missile-nuclear arms control and the rise of asymmetric threats, traditional verification mechanisms have become increasingly ineffective. The study is relevant for scientifically substantiating the transformation of arms control approaches by integrating intelligence tools as a key element to ensure transparency and confidence. The aim of the article is to develop a conceptual model for integrating intelligence support into verification mechanisms for nuclear and missile systems, considering Ukraine’s needs and the current state of international legal regimes. The research employs a complex of general scientific and specialized methods, including systems analysis, analytical, comparative-legal, and synthetic approaches. It examines international agreements, including the Treaty on the Non-Proliferation of Nuclear Weapons and bilateral strategic arms agreements, as well as the use of national technical monitoring means, satellite surveillance, open-source intelligence, and electronic intelligence. The analysis demonstrates that existing verification mechanisms are undergoing a structural crisis due to political paralysis and institutional limitations. Intelligent technologies and big data processing have become the primary source of information for compliance assessment. A three-tier integration model is proposed: organizational level (establishment of an International Nuclear Risk Monitoring Center involving Ukraine, NATO, and the IAEA), technological level (automated satellite data processing, electronic intelligence, and AI-based escalation forecasting), and regulatory level (automation of responses to violations, legally binding data exchange protocols). Integrating intelligence support into international arms control mechanisms allows for a transition from declarative and reactive approaches to preventive risk management. This transformation is especially relevant for non-nuclear states participating in collective security mechanisms, such as Ukraine. The proposed model provides a reliable foundation for building technologically oriented, transparent, and legally grounded arms control systems.